Asymmetric behaviors of interface-stabilized slug pairs in a T-junction microchannel reactor. (31st August 2021) - Wang, Xiaoda; Xia, Jiangnan; Liu, Dayu; Huang, Zhixian; Ge, Xuehui; Zhang, Shuilu; Qiu, Ting
Highlights: Asymmetric behaviors of interface-stabilized slug pairs are investigated. Slug coalescence can be controlled by adjusting different time parameters. Slug coalescence is intensified at high velocity by dislodging stabilizer. Time models are established to describe the effects of stabilizer and asymmetry. Abstract: Critical coalescence condition is a key issue in designing droplet-based microchannel reactors. This study thoroughly examined the coalescence of confined long droplets in T-junction microchannel reactors, focusing on the effects of stabilizer and asymmetry. In addition, the non-coalescence behaviors of slipping and breakup were investigated. Three time parameters, including the film drainage, contact and breakup times, were applied to characterize the coalescence, slipping and breakup behaviors, respectively. The film drainage time had little dependence on the operation conditions in the case of stabilizer-free coalescence, but was affected by superficial velocity and slug length after the addition of stabilizers. Coalescence required a greater film drainage time with a larger arrival time difference. The arrival time difference influenced both the contact and breakup times, whereas the stabilizer concentration had no influence. Models for these time parameters were established. These results will be helpful in accurately controlling the coalescence in T-junction microchannel reactors.